Determining the Requirements and Barriers for Using Barcode Technology in the Hospitals of Tabriz, Iran - Peyman REZAEI-HACHESU; Leila ZYAEI; Hadi HASSANKHANI (Tehran University of Medical Sciences, 2017)
Determining the Requirements and Barriers for Using Barcode Technology in the Hospitals of Tabriz, Iran